2016
DOI: 10.12816/0023824
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Burden in Lebanon : Evolution and Current Status

Abstract: Mycobacterium tuberculosis (MTB) has taken a major global and regional toll [1]. The infectiousness of this pathogen constitutes a serious medical and public health problem. Worldwide deaths due to mortality-related infectious diseases ranked tuberculosis (TB) as the leading cause along with HIV, diarrheal diseases, and acute respiratory infections [1,2]. In 2012, the WHO estimated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 22 publications
3
23
2
1
Order By: Relevance
“…Although Lebanon is considered to have low endemicity with low prevalence of HBV (1.74%) and HCV (0.21%) infections [35, 36], an increasing rate of other infectious diseases such as tuberculosis (TB) and HIV/AIDS [37] is being observed in the Middle East and North African regions and is likely to affect Lebanon [38] due to the influx of nonnationals and refugees.…”
Section: Introductionmentioning
confidence: 99%
“…Although Lebanon is considered to have low endemicity with low prevalence of HBV (1.74%) and HCV (0.21%) infections [35, 36], an increasing rate of other infectious diseases such as tuberculosis (TB) and HIV/AIDS [37] is being observed in the Middle East and North African regions and is likely to affect Lebanon [38] due to the influx of nonnationals and refugees.…”
Section: Introductionmentioning
confidence: 99%
“…This species has been associated with humid weather and water niches, as reported for Cuba, Arizona, Texas, Iran, Gaza and Israel [13]. The humid weather in Lebanon, a Mediterranean costal country, may also explain the high prevalence of M. simiae in this area of the world [13,14]. Few other countries in the Middle East and the Gulf region reported on the recovery of this species, albeit with lower rates such as Oman (8%) and Turkey (2.1%) [8].…”
Section: Discussionmentioning
confidence: 58%
“…Similarly, our study revealed increasing recovery rates of M. simiae, with time: 51% in 2003-2007 to 68% in 2013-2017. This species has been associated with humid weather and water niches, as reported for Cuba, Arizona, Texas, Iran, Gaza and Israel [13]. The humid weather in Lebanon, a Mediterranean costal country, may also explain the high prevalence of M. simiae in this area of the world [13,14].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations